EFEKTIVITAS PROMOSI KESEHATAN MENGENAI PENERAPAN KESEHATAN DAN KESELAMATAN KERJA MELALUI MEDIA VIDEO BERBAHASA SAMBAS PADA KELOMPOK WANITA TANI (KWT) ROSE DI DESA TAMBATAN KABUPATEN SAMBAS - selviana; Ismi Faruqa; Linda Suwarni; Helfi Nolia (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
This study aims to analyze the effectiveness of health promotion regarding the implementation of Occupational Safety and Health (K3) through Sambas language video media in the Rose Women Farmers Group (KWT) in Tamabatan Village, Sambas Regency. The method used was pre-experimental with a one group pretest-posttest design on 30 respondents. Data was collected through observation and questionnaires, then analyzed using the paired t test. The research results showed a significant increase in respondents' knowledge and attitudes after intervention with video media. The mean knowledge score increased from 5.27 to 7.63 (p=0.000), while the mean attitude score increased from 4.20 to 9.27 (p=0.000). This proves that health promotion using local language video media is effective in increasing workers' understanding and awareness of the importance of implementing K3 in the workplace.